Biological Approaches Integrating Algae and Bacteria for the Degradation of Wastewater Contaminants—A Review - Mathew, Merwin Mammen; Khatana, Kanchan; Vats, Vaidehi; Dhanker, Raunak; Kumar, Ram; Dahms, Hans-Uwe; Hwang, Jiang-Shiou (Frontiers in Microbiology, 2022)
The traditional approach to sewage treatment used a consortium of bacterial spp. for the degradation of organic matter. The untreated or partially treated inorganic contaminants result in large amounts of poor quality sludge. The requirement of air input for activated sludge treatment is high energy demanding. So a sustainable technique of sewage treatment that produces less amount of sludge and less energy demand is required for various developed and developing countries. This led to research into using microalgae for wastewater treatment as they reduce concentrations of nutrients like inorganic nitrates and phosphates from the sewage water, hence reducing the associated chemical oxygen demand (COD). Technologies like high-rate algal ponds (HRAPs) came up, that typically use 22% of the electricity used in Sequencing Batch Reactors for activated sludge treatment with added economic and environmental benefits like reduced comparative operation cost per cubic meter, lower global warming and eutrophication potentials . The microalgal growth also helps in the removal of toxic heavy metals like Al, Ni, Cu etc. which could be further optimized by the acid treatment of the cells. Their growth also creates the potential for the production of biofuels and bioproducts from their biomass. The addition of suitable bacterial species may further enhance the treatment potential to the waste water medium. This happens as the inorganic nutrients are assimilated into the algal biomass while the organic nutrients are utilized by bacteria. Further the mutualistic exchange of CO2 and O2 between the algae and the bacteria helps intensify the photosynthetic activity of algae and oxidation by bacteria leading to a higher overall nutrient removal efficiency. Even negative interactions between algae and bacteria mediated by various secondary metabolites (phycotoxins) prove to be beneficial eutrophic water bodies as loads of algal blooms are controlled. The present review aims to give the reader a critical idea of this method of wastewater treatment that integrates microalgae and bacteria.